2003
DOI: 10.1046/j.1462-2920.2003.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Vibrio cholerae phage isolated from the coastal water of Peru

Abstract: A Vibrio cholerae bacteriophage, family Myoviridae, was isolated from seawater collected from the coastal water of Lima, Peru. Genome size was estimated to be 29 kbp. The temperate phage was specific to V. cholerae and infected 12/13 V. cholerae O1 strains and half of the four non-O1/non-O139 strains tested in this study. Vibrio cholerae O139 strains were resistant to infection and highest infection rates were obtained in low nutrient media amended with NaCl or prepared using seawater as diluent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Three vibriophages, AS 1 , AS 2 , and AS 3 were isolated from the sewage and pond waters of the outskirts of Kolkata, phages AS 1 and AS 2 had hexagonal heads and contractile tails and were of the family of Myoviridae [4]. Other studies have showed that a V. cholerae bacteriophages isolated from the sea water collected from the coastal water of Lima, Peru, belonged to the family of Myoviridae [17]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three vibriophages, AS 1 , AS 2 , and AS 3 were isolated from the sewage and pond waters of the outskirts of Kolkata, phages AS 1 and AS 2 had hexagonal heads and contractile tails and were of the family of Myoviridae [4]. Other studies have showed that a V. cholerae bacteriophages isolated from the sea water collected from the coastal water of Lima, Peru, belonged to the family of Myoviridae [17]. …”
Section: Resultsmentioning
confidence: 99%
“…Phages infecting V. cholerae are well documented with earliest records of isolation of bacteriophages appearing in 1920s [17]. In V. cholerae bacteriophages were first reported by Siddiqui and Bhattacharyya [13].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in phage numbers in the environment was also correlated with an increase in V. cholerae lytic bacteriophage in patient stool samples, with one of the predominant bacteriophage species belonging to the Myoviridae family (Seed et al, 2011). Environmental surveys have detected Myoviridae in regions where cholera outbreaks have occurred, such as Peru (Talledo et al, 2003), Kolkata (Sen and Ghosh, 2005), and Kenya (Maina et al, 2013). Control of V. cholerae by phage is supported by a continuous culture experiment, which suggests that V. cholerae populations may be influenced by phage to a larger extent than by nutrient limitation (Wei et al, 2011).…”
Section: Top-down Control By Predatory Micrograzersmentioning
confidence: 99%
“…Morphological analysis by transmission electron microscopy showed that bacteriophage VPUSM 8 belongs to the Myoviridae family (1, 4), while the genome sequence suggests that it is a P2-like bacteriophage (5). The genome of VPUSM 8 was 34,145 bp, with a G+C content of 48.92% and 43 identified CDSs.…”
Section: Genome Announcementmentioning
confidence: 99%